Preparation process of polypropylene micro-plastic
Modified nanosilica and maleic anhydride modified carbon by using N,N'-dicyclohexylterephthalamide, 3-(methacryloyloxy)propyltrimethoxysilane in polypropylene microplastics Black solves the problem of insufficient toughness of polypropylene microplastics and achieves the high toughness and anti-aging effects of the material.
Patent Information
- Application Number
- CN202510022034.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2045-01-07
AI Technical Summary
Polypropylene microplastics have poor toughness, aging and impact resistance, resulting in the products being easily broken and damaged when impacted by external forces.
The crystal form of polypropylene is regulated by using N,N'-dicyclohexylterephthalamide as nucleating agent, and modified nanosilica and horses with 3-(methacryloyloxy)propyltrimethoxysilane. It can modify carbon black with acid anhydride to improve the toughness and anti-aging ability of polypropylene microplastics.
It significantly improves the toughness and anti-aging ability of polypropylene microplastics, enhances its tolerance to external impacts, and extends the service life of the material.
Smart Images

Figure CN119410070A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of organic synthesis and relates to a preparation process of polypropylene, in particular to a preparation process of polypropylene microplastics. Background Art
[0002] Polypropylene (PP) is a thermoplastic resin and one of the five general-purpose plastics. It is widely used in various fields because of its non-toxic, odorless, light density (0.90g / cm³, the lightest general-purpose plastic), easy processing, good impact strength, strong flexural resistance and good electrical insulation. Polypropylene in the form of microplastics also has many uses. Polypropylene microplastics are food-grade plastics and are often used to make food containers and packaging materials such as lunch boxes, kettles, baby bottles, foam plastic boxes, and PP plastic cups. Polypropylene microplastics can also be used to make plastic woven products, such as container bags, woven bags, food bags, and transparent bags. These products are widely used in the packaging of products such as grain, fertilizers, and cement. Relying on the non-toxic and high-temperature resistant properties of polypropylene microplastics, it is widely used in the manufacture of pipes in the fields of water supply and heating systems. Compared with PE pipes, PP pipes are lighter, easier to transport, and have better environmental protection performance and can be recycled. This makes PP pipes highly competitive in the market. In addition to the above main application areas, polypropylene microplastics are also used to make various other products, such as medical equipment, stationery, sporting goods, etc. These products also take advantage of the excellent properties of polypropylene, such as chemical corrosion resistance and easy processing. In summary, polypropylene microplastics are widely used in various fields due to their various excellent properties. However, the toughness, aging resistance and impact resistance of polypropylene materials are poor, making the products easy to break and damage when subjected to external impact. Therefore, improving the toughness of polypropylene microplastics will help improve the application of polypropylene microplastics. Summary of the invention
[0003] In view of the above problems, the present invention designs a preparation process of polypropylene microplastics; the process specifically comprises the following steps: S1. Weigh 70-100g of polypropylene particles and 0.1-0.4g of N,N'-dicyclohexyl terephthalamide, melt mix and blend evenly, and then use a single screw extruder to form a crude masterbatch. The extrusion temperature and pressure are 200-260°C and 10-16Mpa, respectively. The β-nucleation effect of N,N'-dicyclohexyl terephthalamide regulates the crystal form of polypropylene and thus enhances the toughness of polypropylene.
[0004] S2, modified nano-silica: anhydrous ethanol, deionized water, 3-(methacryloyloxy)propyltrimethoxysilane, and nano-silica are added to a three-necked flask in a mass ratio of 10:10:5:1, and stirred at room temperature to evenly disperse the silica. Then microwave heating to 50-80 ° C, while condensing and refluxing for 2-5h. After the reaction is completed, the filter cake is obtained by suction filtration with anhydrous ethanol, and the filter cake is placed in a vacuum drying oven at 50-80 ° C and dried for 8-14h. The dried filter cake is ground to obtain the modified silica powder. The mechanism of action of this step is that the methoxy group in the 3-(methacryloyloxy)propyltrimethoxysilane molecule is hydrolyzed to generate a hydroxyl group and undergoes a dehydration condensation reaction with the silanol group on the surface of the nano-silica, reducing the surface polarity of the nano-silica, reducing the agglomeration of the nano-silica, and improving the compatibility of the nano-silica with polypropylene, thereby improving the dispersibility of the nano-silica in polypropylene. Nano-silica further enhances the toughness of polypropylene microplastics through interfacial interactions.
[0005] S3. Modified carbon black: weigh 2-8g of carbon black and 6-12g of maleic anhydride, dissolve them in 100ml of acetone, and stir them with a magnetic stirrer at room temperature for 1-2h. After stirring, the carbon black obtained by vacuum filtration is placed in an oven for drying for 2-8h. The obtained carbon black is then transferred to a porcelain boat and placed in a muffle furnace at 160-220℃ for 1.5-3h to obtain carbon black grafted with maleic anhydride; under the action of high temperature, the anhydride groups in maleic anhydride react with the hydroxyl and carboxyl groups on the surface of carbon black to form ester bonds, thereby increasing the compatibility of carbon black with polypropylene.
[0006] S4, the masterbatch obtained in step S1, the modified nano-silicon dioxide obtained in step S2 and the modified carbon black obtained in step S3 are mixed evenly in a ratio of 2:1:1, and then melt-extruded and granulated on a twin-screw extruder at 200-350 rpm and 190-220° C. After the granules are cooled to room temperature, they are poured into a crusher and crushed at 600-900 rpm for 1-4 hours, and a sieve aperture of 5 mm is used to ensure that the microplastic level is reached.
[0007] Preferably, in step S1, 90 g of polypropylene particles are weighed; Preferably, the extrusion temperature in step S1 is 220°C; Preferably, the extrusion pressure in step S1 is 12 Mpa; Preferably, the condensation reflux reaction in step S2 is performed for 4 hours; Preferably, in step S3, 6 g of carbon black is weighed; Preferably, the insulation temperature in step S3 is 180°C; Preferably, the speed of the twin-screw extruder in step S4 is 300 rpm; Preferably, the extrusion temperature in step S4 is 200°C; Compared with the prior art, the present invention has the following beneficial effects: The present invention uses N,N'-dicyclohexyl terephthalamide nucleating agent to induce polypropylene to transform into beta-crystalline polypropylene, and the beta-crystalline has excellent toughness.
[0008] The present invention uses 3-(methacryloyloxy)propyltrimethoxysilane to modify nano-silica. The methoxy groups in the 3-(methacryloyloxy)propyltrimethoxysilane molecules are hydrolyzed to generate hydroxyl groups, which react with the silanol groups on the surface of the nano-silica to undergo a dehydration condensation reaction, thereby reducing the surface polarity of the nano-silica, thereby facilitating the uniform dispersion of the nano-silica in polypropylene. The nano-silica further enhances the toughness of the polypropylene microplastics through interface interaction.
[0009] Maleic anhydride modified carbon black increases the compatibility of carbon black with polypropylene, and its synergistic effect with modified nano-silica improves the anti-aging ability of polypropylene microplastics. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 This is a graph showing the tensile yield strength of the polypropylene microplastic strips in Example 1 and Comparative Examples 1-3 of the present invention.
[0011] Figure 2 This is a cross-sectional scanning electron microscope image of the polypropylene microplastic particles in Comparative Example 6 of the present invention.
[0012] Figure 3 This is a cross-sectional scanning electron microscope image of the polypropylene microplastic particles in Example 3 of the present invention.
[0013] Figure 4 This is a graph of the impact strength of the polypropylene microplastic strips in Example 4 of the present invention and Comparative Examples 7-9. DETAILED DESCRIPTION
[0014] Exemplary embodiments, features and performance aspects of the present invention will be described in detail below with reference to the accompanying drawings.
[0015] In the present invention, polypropylene particles are from Qingdao Juli New Energy Technology Co., Ltd., N,N'-dicyclohexyl terephthalamide is from Hubei Shuaiyan Ligao Biomedicine Co., Ltd., 3-(methacryloyloxy)propyltrimethoxysilane is from Hubei Hengjingrui Chemical Co., Ltd., nano-scale silicon dioxide is from Fujian Xinhe Nano Silicon Co., Ltd., carbon black is from Jiangxi Black Cat Carbon Black Co., Ltd., and maleic anhydride is from Hubei Keward Chemical Co., Ltd.
[0016] Example 1
[0017] S1. Weigh 70g of polypropylene pellets and 0.1g of N,N'-dicyclohexyl terephthalamide, melt mix and blend evenly, and then use a single screw extruder to make a crude masterbatch. The extrusion temperature and pressure are 200℃ and 10Mpa, respectively. The β-nucleation effect of N,N'-dicyclohexyl terephthalamide regulates the crystal form of polypropylene and thus enhances the toughness of polypropylene.
[0018] S2, modified nano-silica: anhydrous ethanol, deionized water, 3-(methacryloyloxy)propyltrimethoxysilane, and nano-silica are added to a three-necked flask in a mass ratio of 10:10:5:1, and stirred at room temperature to evenly disperse the silica. Then microwave heating to 50 ° C, while condensing and refluxing for 2 hours. After the reaction is completed, the filter cake is filtered with anhydrous ethanol, and the filter cake is placed in a vacuum drying oven at 50 ° C and dried for 8 hours. The dried filter cake is ground to obtain the modified silica powder. The mechanism of action of this step is that the methoxy group in the 3-(methacryloyloxy)propyltrimethoxysilane molecule is hydrolyzed to generate hydroxyl groups, which react with the silanol groups on the surface of nano-silica through dehydration condensation, reducing the surface polarity of nano-silica, reducing the agglomeration of nano-silica, and improving the compatibility of nano-silica with polypropylene, thereby improving the dispersibility of nano-silica in polypropylene. Nano-silica further enhances the toughness of polypropylene microplastics through interfacial interaction.
[0019] S3. Modified carbon black: Weigh 2g of carbon black and 6g of maleic anhydride, dissolve them in 100ml of acetone, and stir them with a magnetic stirrer at room temperature for 1h. After stirring, the carbon black obtained by vacuum filtration is placed in an oven and dried for 2h. The obtained carbon black is then transferred to a porcelain boat and placed in a muffle furnace at 160℃ for 1.5h to obtain carbon black grafted with maleic anhydride.
[0020] S4, the masterbatch obtained in step S1, the modified nano-silica obtained in step S2 and the modified carbon black obtained in step S3 are mixed evenly in a ratio of 2:1:1, and then melt-extruded and granulated on a twin-screw extruder at 200 rpm and 190° C. After the granules are cooled to room temperature, they are poured into a crusher and crushed at 600 rpm for 1 hour, and a sieve aperture of 5 mm is used to ensure that they reach the microplastic level.
[0021] Comparative Example 1: Except that calcium carbonate is used in step S1 instead of N,N'-dicyclohexylterephthalamide, the other steps are the same as those in Example 1.
[0022] Comparative Example 2: Except that calcium pimelate was used in step S1 instead of N,N'-dicyclohexylterephthalamide, the other steps were the same as those in Example 1.
[0023] Comparative Example 3: Except that sodium carboxylate is used in step S1 instead of N,N'-dicyclohexylterephthalamide, the other steps are the same as those in Example 1.
[0024] The polypropylene microplastics prepared in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 were melt-extruded into strips with a size of 60 mm*10 mm*1 mm, and the tensile yield strength was tested using a universal material testing machine at room temperature and a pulling rate of 1 mm / min. The results are as follows: Figure 1 As shown, Figure 1 The main reason why the tensile yield strength of Comparative Example 1 is lower than that of Example 1 is that the calcium carbonate β nucleation induction efficiency is low and it is not easy to disperse in polypropylene. The tensile strength of the polypropylene strips prepared in Comparative Examples 2 and 3 is lower than that of Example 1. The fundamental reason is that there is a hydrogen bond between N, N'-dicyclohexyl terephthalamide and the modified nano-silica, which further reduces the surface energy of the nano-silica. The two synergistically promote the dispersibility of nano-silica in polypropylene microplastics and improve the toughness of polypropylene microplastics.
[0025] Example 2
[0026] S1. Weigh 80g of polypropylene pellets and 0.2g of N,N'-dicyclohexyl terephthalamide, melt mix and blend evenly, and then use a single screw extruder to make a crude masterbatch. The extrusion temperature and pressure are 220℃ and 12Mpa, respectively. The β-nucleation effect of N,N'-dicyclohexyl terephthalamide regulates the crystal form of polypropylene and thus enhances the toughness of polypropylene.
[0027] S2, modified nano-silica: anhydrous ethanol, deionized water, 3-(methacryloyloxy)propyltrimethoxysilane, and nano-silica are added to a three-necked flask in a mass ratio of 10:10:5:1, and stirred at room temperature to evenly disperse the silica. Then microwave heating to 60 ° C, while condensing and refluxing for 3 hours. After the reaction is completed, the filter cake is filtered with anhydrous ethanol, and the filter cake is placed in a vacuum drying oven at 60 ° C and dried for 10 hours. The dried filter cake is ground to obtain the modified silica powder. The mechanism of action of this step is that the methoxy group in the 3-(methacryloyloxy)propyltrimethoxysilane molecule is hydrolyzed to generate a hydroxyl group, which reacts with the silanol group on the surface of nano-silica through dehydration condensation, reducing the surface polarity of nano-silica, reducing the agglomeration of nano-silica, and improving the compatibility of nano-silica with polypropylene, thereby improving the dispersibility of nano-silica in polypropylene. Nano-silica further enhances the toughness of polypropylene microplastics through interfacial interaction.
[0028] S3, modified carbon black: weigh 4g carbon black and 8g maleic anhydride, dissolve them in 100ml acetone, stir them with a magnetic stirrer at room temperature for 1.5h, vacuum filter the obtained carbon black and put it into an oven for drying for 4h, then transfer the obtained carbon black into a porcelain boat and place it in a muffle furnace at 180℃ for 2h to obtain maleic anhydride grafted carbon black; S4, the masterbatch obtained in step S1, the modified nano-silica obtained in step S2 and the modified carbon black obtained in step S3 are mixed evenly in a ratio of 2:1:1, and then melt-extruded and granulated on a twin-screw extruder at 250 rpm and 200° C. After the granules are cooled to room temperature, they are poured into a crusher and crushed at 700 rpm for 2 hours, using a 5 mm sieve aperture to ensure that they reach the microplastic level.
[0029] Comparative Example 4: Except that 3-(methacryloyloxy)propyltrimethoxysilane is not added in step S2, the other steps are the same as those in Example 2.
[0030] Comparative Example 5: Except that ethylene glycol is used in step S2 instead of 3-(methacryloyloxy)propyltrimethoxysilane, the other steps are the same as those in Example 2.
[0031] The polypropylene microplastic particles prepared in Example 2, Comparative Example 4 and Comparative Example 5 were respectively subjected to flattening tests. During the flattening test, the polypropylene microplastic particles were placed between two parallel plates and pressed evenly with a press to observe whether they were deformed. The power of the press was 2.5KW, the pressing speed was 50um / s, and the fixed load was 20N. The results are shown in Table 1.
[0032] Table 1
[0033] It can be seen from Table 1 that in the fixed load pressure test, Comparative Example 4, which does not use 3-(methacryloyloxy)propyltrimethoxysilane, has uneven dispersion in polypropylene microplastics due to the polarity of nano-silicon dioxide, thus causing particle breakage. It can be seen from Comparative Example 5 in Table 1 that ethylene glycol has a certain effect on reducing the polarity of nano-silicon dioxide, which is greatly improved compared to Comparative Example 4. Example 2 shows that polypropylene microplastic particles modified with 3-(methacryloyloxy)propyltrimethoxysilane can still maintain a good round particle shape, which is mainly because 3-(methacryloyloxy)propyltrimethoxysilane enhances the interfacial bonding between nano-silicon dioxide and polypropylene, thereby improving the toughness of the particles.
[0034] Example 3
[0035] S1. Weigh 90g of polypropylene pellets and 0.3g of N,N'-dicyclohexyl terephthalamide, melt mix and blend evenly, and then use a single screw extruder to make a crude masterbatch. The extrusion temperature and pressure are 240°C and 14Mpa, respectively. The β-nucleation effect of N,N'-dicyclohexyl terephthalamide regulates the crystal form of polypropylene and thus enhances the toughness of polypropylene.
[0036] S2, modified nano-silica: anhydrous ethanol, deionized water, 3-(methacryloyloxy)propyltrimethoxysilane, and nano-silica are added to a three-necked flask in a mass ratio of 10:10:5:1, and stirred at room temperature to evenly disperse the silica. Then microwave heating to 70 ° C, while condensing and refluxing for 4 hours. After the reaction is completed, the filter cake is filtered with anhydrous ethanol, and the filter cake is placed in a vacuum drying oven at 70 ° C and dried for 12 hours. The dried filter cake is ground to obtain the modified silica powder. The mechanism of action of this step is that the methoxy group in the 3-(methacryloyloxy)propyltrimethoxysilane molecule is hydrolyzed to generate hydroxyl groups, which react with the silanol groups on the surface of nano-silica through dehydration condensation, reducing the surface polarity of nano-silica, reducing the agglomeration of nano-silica, and improving the compatibility of nano-silica with polypropylene, thereby improving the dispersibility of nano-silica in polypropylene. Nano-silica further enhances the toughness of polypropylene microplastics through interfacial interaction.
[0037] S3, modified carbon black: weigh 6g of carbon black and 10g of maleic anhydride, dissolve them in 100ml of acetone, stir them with a magnetic stirrer at room temperature for 1.5h, vacuum filter the obtained carbon black after stirring, put it into an oven for drying for 6h, and then transfer the obtained carbon black into a porcelain boat and place it in a muffle furnace at 200℃ for 2.5h to obtain carbon black grafted with maleic anhydride; S4, the masterbatch obtained in step S1, the modified nano-silicon dioxide obtained in step S2 and the modified carbon black obtained in step S3 are mixed evenly in a ratio of 2:1:1, and then melt-extruded and granulated on a twin-screw extruder at 300 rpm and 210° C. After the granules are cooled to room temperature, they are poured into a crusher and crushed at 800 rpm for 3 hours, and a sieve aperture of 5 mm is used to ensure that they reach the microplastic level.
[0038] Comparative Example 6: Except that N,N'-dicyclohexylterephthalamide is not added in step S1, the other steps are the same as those in Example 3.
[0039] Figure 2 The cross-sectional view of the polypropylene microplastic prepared in Comparative Example 6 shows that the cross section is relatively smooth and exhibits brittle fracture. Figure 3This is a cross-sectional view of the polypropylene microplastic prepared in Example 3. A large number of band structures can be seen in the figure. This is mainly because N,N'-dicyclohexylterephthalamide hinders the relaxation of the polypropylene molecular chain and thus produces a large number of band structures. This structure further improves the toughness of the material.
[0040] Example 4
[0041] S1. Weigh 100g of polypropylene pellets and 0.4g of N,N'-dicyclohexyl terephthalamide, melt mix and blend evenly, and then use a single screw extruder to make a crude masterbatch. The extrusion temperature and pressure are 260°C and 16Mpa, respectively. The β-nucleation effect of N,N'-dicyclohexyl terephthalamide regulates the crystal form of polypropylene and thus enhances the toughness of polypropylene.
[0042] S2, modified nano-silica: anhydrous ethanol, deionized water, 3-(methacryloyloxy)propyltrimethoxysilane, and nano-silica are added to a three-necked flask in a mass ratio of 10:10:5:1, and stirred at room temperature to evenly disperse the silica. Then microwave heating to 80 ° C, while condensing and refluxing for 5 hours. After the reaction is completed, the filter cake is filtered with anhydrous ethanol, and the filter cake is placed in a vacuum drying oven at 80 ° C and dried for 14 hours. The dried filter cake is ground to obtain the modified silica powder. The mechanism of action of this step is that the methoxy group in the 3-(methacryloyloxy)propyltrimethoxysilane molecule is hydrolyzed to generate a hydroxyl group, which reacts with the silanol group on the surface of nano-silica through dehydration condensation, reducing the surface polarity of nano-silica, reducing the agglomeration of nano-silica, and improving the compatibility of nano-silica with polypropylene, thereby improving the dispersibility of nano-silica in polypropylene. Nano-silica further enhances the toughness of polypropylene microplastics through interfacial interaction.
[0043] S3, modified carbon black: weigh 8g of carbon black and 12g of maleic anhydride, dissolve them in 100ml of acetone, stir them with a magnetic stirrer at room temperature for 2h, vacuum filter the obtained carbon black and put it into an oven for drying for 8h, then transfer the obtained carbon black into a porcelain boat and place it in a muffle furnace at 220℃ for 3h to obtain maleic anhydride grafted carbon black; S4, the masterbatch obtained in step S1, the modified nano-silicon dioxide obtained in step S2 and the modified carbon black obtained in step S3 are mixed evenly in a ratio of 2:1:1, and then melt-extruded and granulated on a twin-screw extruder at 350 rpm and 220° C. After the granules are cooled to room temperature, they are poured into a crusher and crushed at 900 rpm for 4 hours, using a 5 mm sieve aperture to ensure that they reach the microplastic level.
[0044] Comparative Example 7: Except that maleic anhydride is not added in step S3, the remaining steps are the same as those in Example 4.
[0045] Comparative Example 8: Except that the dried carbon black in step S3 is not calcined in a muffle furnace, the remaining steps are the same as those in Example 4.
[0046] Comparative Example 9: Except that the modified nano-silicon dioxide obtained in step S2 is replaced by unmodified nano-silicon dioxide in step S4, the other steps are the same as those in Example 4.
[0047] The polypropylene microplastics prepared in Example 4, Comparative Example 7, Comparative Example 8, and Comparative Example 9 were melt-extruded into strips with a size of 80 mm*10 mm*4 mm and an A-type notch. The strips were placed in a xenon lamp aging box for 960 hours and then taken out for a cantilever beam notched impact strength test with an impact hammer energy of 22 J. The results are shown in FIG. Figure 4 As shown, the impact strength of Comparative Example 7 without the addition of maleic anhydride is greatly reduced due to the poor compatibility of carbon black in polypropylene. Comparative Example 8 did not perform the muffle furnace calcination process to treat carbon black, which greatly reduced the effect of maleic anhydride grafting, so the impact strength was not much different from that of Comparative Example 7. However, Example 4 modified with maleic anhydride has significantly better impact strength than Comparative Examples 7 and 8. Comparative Example 9 shows that the modified nano-silica also makes an outstanding contribution to the anti-aging ability of the material, mainly because the ability of the modified nano-silica to absorb ultraviolet rays is enhanced. Benefiting from the strong ability of modified carbon black and modified nano-silica to absorb ultraviolet rays on the surface of polypropylene microplastic particles, the anti-aging performance of the material is improved, so its impact strength is relatively high.
[0048] Finally, it should be noted that the above-described embodiments are only used to illustrate the technical solution of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solution described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solution to deviate from the scope of the technical solution of the embodiments of the present invention.
Claims
1. A process for preparing polypropylene microplastics, characterized in that: The specific preparation method is as follows: S1, weighing 70-100g of polypropylene particles and 0.1-0.4g of N,N'-dicyclohexylterephthalamide, melt-mixing and uniformly blending, and then using a single-screw extruder to form a crude masterbatch, the extrusion temperature and pressure are 200-260°C and 10-16Mpa respectively; S2, modified nano-scale silica: anhydrous ethanol, deionized water, 3-(methacryloyloxy)propyltrimethoxysilane, and nano-scale silica are added into a three-necked flask in a mass ratio of 10:10:5:1, and stirred at room temperature to evenly disperse the silica; then microwave heating is performed to 50-80°C, and condensation reflux reaction is performed for 2-5 hours; after the reaction is completed, anhydrous ethanol is used for suction filtration to obtain a filter cake, and the filter cake is placed in a vacuum drying oven at 50-80°C and dried for 8-14 hours. The dried filter cake can be ground to obtain the modified silica powder; S3, modified carbon black: weigh 2-8g carbon black and 6-12g maleic anhydride, dissolve in 100ml acetone, stir with a magnetic stirrer at room temperature for 1-2h, vacuum filter the obtained carbon black and put it into an oven for drying for 2-8h, then transfer the obtained carbon black into a porcelain boat and place it in a muffle furnace at 160-220℃ for 1.5-3h to obtain maleic anhydride grafted carbon black; S4. The masterbatch obtained in step S1, the modified nano-silica obtained in step S2 and the modified carbon black obtained in step S3 are uniformly mixed in a ratio of 2:1:1, and then melt-extruded into granules on a twin-screw extruder at 200-350 rpm and 190-220°C; after the granules are cooled to room temperature, they are poured into a crusher and crushed at 600-900 rpm for 1-4 hours, using a sieve aperture of 5 mm to ensure that the granules reach the microplastic level.
2. A process for preparing polypropylene microplastics according to claim 1, characterized in that: In the step S1, 90 g of polypropylene particles are weighed.
3. The process for preparing polypropylene microplastics according to claim 1, characterized in that: The extrusion pressure in step S1 is 12 Mpa.
4. The process for preparing polypropylene microplastics according to claim 1, characterized in that: In step S2, microwave heating is performed to 60°C.
5. The process for preparing polypropylene microplastics according to claim 1, characterized in that: In step S2, the condensation reflux reaction is carried out for 4 hours.
6. The process for preparing polypropylene microplastics according to claim 1, characterized in that: In the step S3, 6 g of carbon black is weighed.
7. The process for preparing polypropylene microplastics according to claim 1, characterized in that: The insulation temperature in step S3 is 180°C.
8. The process for preparing polypropylene microplastics according to claim 1, characterized in that: In step S4, the speed of the twin-screw extruder is 300 rpm.
9. The process for preparing polypropylene microplastics according to claim 1, characterized in that: The extrusion temperature in step S4 is 200°C.
10. Polypropylene microplastics obtained by the preparation process of polypropylene microplastics according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of polypropylene beta crystallographic form nucleater
CN101585928A
Polymer-grafted graphene oxide master batch and preparation method thereof
CN104371115A
Preparation method for nano silicon dioxide modified polypropylene
CN109438843A
Flame-retardant beta-cyclodextrin modified polypropylene-based cellulose hydrogel and preparation method thereof
CN111592666A
Anti-corrosion high-temperature-resistant polymeric membrane material for sucker rod and preparation process thereof
CN116004070A
Cited By
Reinforced polyolefin resin composite fiber and preparation method thereof
CN120945504A